LOOK AND SAY METHOD FOR IMPROVING READING COMPREHENSION OF THE TWELFTH GRADE STUDENTS - Dwi Riyanti; Uli Rohali; Semi Sukarni (Wiralodra English Journal, 2025)
Based on the initial observation, many Senior High School students are lack of motivation in reading English texts. One of the reasons is because the students do not understand the vocabulary use in the text, parcularly when the text a bit long. This study aims to improve students' reading comprehension skills through the Look and Say method. This study uses the Classroom Action Research (CAR) approach consisting of four stages: planning, implementing, observation, and reflection. Participants in this study were grade XII students of SMA N 5 Purworejo. The subjects of this study were twelfth-grade students which consisted of 35 students, 10 of them are male and 15 students are female. Data were collected through observation and tests, then analyzed using descriptive analysis techniques. The results showed a significant increase in students' reading skills after the application of the Look and Say method. The increase was seen from the pre-cycle stage to cycle 1, and from cycle 1 to cycle 2. The average score increased from 63.52 in the pre-cycle, to 68.28 in cycle 1, and 71.42 in cycle 2. This indicates that the Look and Say method is effective in improving students' reading skills.